Application of computational fluid dynamics in the study of the caribbean petroleum corporation gasoline vapour dispersion. (July 2021) - Alutu, Chimaobi; El-Hassan, Zaki; Leslie, Tony; Durrant, Andy; Rodriguez, Cristina
Abstract: Computational Fluid Dynamics (CFD) is used to predict the dispersion of a gasoline vapour cloud. The model was validated using the results of the analysis of Buncefield incident (2005) in the UK and a new method of simulation that involves the interaction of liquid fuel and air during the dispersion was introduced. The Caribbean Petroleum Corporation (CAPECO) incident (2009) was simulated using the developed CFD modelling method. The results of CFD analysis of this incident focused on the release of flammable liquid fuels that was followed by the formation of vapour clouds. The effect of wind speed and the gasoline evaporation surface area were analysed. The CFD simulations showed that the main factors affecting the dispersion and behaviour of the vapour clouds are release surface area, wind speed, topography, turbulence and obstacles in the area. The simulation results showed similar behaviour to that observed in the real-life incidents in terms of the vapour cloud behaviour and the extent of damage. This work used the realizable k − ε model which was previously validated for the dispersion of dense gases. This turbulence model was helpful in the study of the wind speed (nil to low) characteristics of the CAPECO dispersion accident and the dispersion of the liquid gasoline droplets was successfully simulated using ANSYS FLUENT's built-in Discrete Phase Model (DPM). This work simulated evaporation of gasoline liquid and droplet dispersion in a wide area and from a large source with the presence of obstacles. Dispersion of the gasoline droplets was successfully accounted for by the inclusion of the DPM sub-models for cloud dispersion, namely, the stochastic tracking and the Discrete Random Walk model (DRW). It could be concluded that this work validates the feasibility of using the DPM sub-model application for the simulation of volatile liquids evaporation and dispersion through a domain that includes several obstacles and high levels of congestion.